AN HISTORICAL APPROACH TO THE RELATIONSHIP BETWEEN EXCESS AUDITOR REMUNERATION AND AUDIT QUALITY: DO THE ROLES OF AUDITOR ATTRIBUTES MATTER? - Alexander Olawumi Dabor; Emhenya Anthony Iyoha; Godwin Ohiokha; A-Oghoye I. Iyoha (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The expansion of business in the twelfth-century necessitated the need for engagement of the services of auditors to curtail the excesses of management. The objective of this study is to examine the moderating effects of auditor attributes on the relationship between excess auditor remuneration and audit quality. Precisely the study examines the moderating effects of auditor tenure, auditor independence, and audit firm size on the relationship between excess auditor remuneration and audit quality. This study employed simple random sampling techniques to select fifty-two quoted Nigerian companies and data were extracted from the financial reports of the selected companies for fifteen years (2006-2020). The study employed the least square regression technique. The results showed that there is no significant relationship between excess audit pricing and audit quality. The result also showed that auditor tenure and audit firm size have a negative moderating influence on the relationship between excess audit remuneration and audit quality while auditor independence has a positive influence on the relationship between excess audit remuneration and audit quality. This study recommended that elongated auditor tenure should be discouraged to enhance quality audit and audit firms should be discouraged from charging a fee that may impair auditor independence.